Writing Tales of the Future: Five “Balancing Acts” for Globographers - Næss, Hans Erik (Qualitative Sociology Review, 2021)
Since the early 1990s much has been written about how ethnographers should do fieldwork of the local in a globalizing world. The challenge of communicating their analyses authentically in a world of information overload is much less debated. To rectify this situation, I argue in this paper that five balancing acts are crucial to those who do ethnographies of the global, or “globographers,” in their writing. Emerging from a review of the history of fieldwork and writing, these balancing acts constitute a template of how a communicative consciousness may assist qualitative researchers in achieving ethnographic integrity.